Politik Pendidikan Agama di Indonesia dan Pelaksanaannya di Salah Satu Kampus Katolik di Flores - Fransiska Widyawati; Yohanes S Lon (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
Religious education has been one of most controversial problems debated in the drafting of laws relation to education and religion in the history of Indonesia. Since the establishment of the nation, the position of religious education in school has been questioned. This debate arose in particular because many private schools organized by religious communities, institutions and foundations, especially the Christians/Catholics, only gave Christian/Catholic religious education to all the students, including to the Muslims. This research explores the social and political context of this issue and specifically looks at its practices in the contemporary era on one of the Catholic campuses in Flores. This study used a qualitative approach by combining text and context analysis. Specifically for field data obtained by in-depth interviews and FGDs on a number of Catholic school organizers, school principals, teachers and non-Catholic students who take part in Catholic religious studies. This study found that when the issue of religious instruction in schools was discussed, the debate should not only be directed at what religious lessons were given to students but rather on what religious lessons students should receive from any religion that could help students to be able to overcome the problems of society, nation and state specifically in the context of pluralism.